2018
DOI: 10.3390/genes9120581
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Cohesin in the DNA Damage Response

Abstract: Faithful transmission of genetic material is crucial for all organisms since changes in genetic information may result in genomic instability that causes developmental disorders and cancers. Thus, understanding the mechanisms that preserve genome integrity is of fundamental importance. Cohesin is a multiprotein complex whose canonical function is to hold sister chromatids together from S-phase until the onset of anaphase to ensure the equal division of chromosomes. However, recent research points to a crucial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 220 publications
2
56
1
Order By: Relevance
“…Although cohesin functions to prevent premature sister chromosome segregation during mitosis, it also functions in organizing the 3D genome within interphase cells 46 , which has critical implications for DNA replication 47 , DNA repair 48 , gene transcription 49 and telomere maintenance 50 . Thus, although our primary focus was on numerical CIN resulting from PGCs (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Although cohesin functions to prevent premature sister chromosome segregation during mitosis, it also functions in organizing the 3D genome within interphase cells 46 , which has critical implications for DNA replication 47 , DNA repair 48 , gene transcription 49 and telomere maintenance 50 . Thus, although our primary focus was on numerical CIN resulting from PGCs (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic analysis and subsequent validation experiments showed that DCAF15 loaded into CLR4 complexes, interacted with cohesin complex members SMC1 and SMC3, and promoted their ubiquitination. We were intrigued by these interactions given the similar CRISPR screening scoring pattern of DCAF15 to the cohesin factors STAG2 and HDAC8 (Figure 2E); the shared roles of cohesin and CRL4 E3 ligases in DNA metabolism, organization, replication and repair 34, 59, 60 ; and the ability of cohesin mutations to dysregulate hematopoietic differentiation in myeloid malignancies 35 . Rather than globally controlling SMC protein levels, we speculate that CRL4-DCAF15 complexes ubiquitinate cohesin at specific genomic sites to regulate chromatin topology or repair (Figure 7G).…”
Section: Discussionmentioning
confidence: 99%
“…These lysine acetyltransferases have recently been shown to be important for acetylating proteins involved in the DDR and DNA repair 40 . NIPBL and cohesin are also both involved in DNA damage signalling and repair 41 and CdLS patient cells carrying NIPBL mutations display an increased DNA damage sensitivity 7 . Furthermore, we show an increase in 53BP1 foci number and size, similar to that seen in BRD4 Y430C mESCs, in NIPBL haploinsufficient LCLs.…”
Section: Discussionmentioning
confidence: 99%